2017
DOI: 10.1126/scitranslmed.aah5642
|View full text |Cite
|
Sign up to set email alerts
|

Individuals with progranulin haploinsufficiency exhibit features of neuronal ceroid lipofuscinosis

Abstract: Heterozygous mutations in the GRN gene lead to progranulin (PGRN) haploinsufficiency and cause frontotemporal dementia (FTD), a neurodegenerative syndrome of older adults. Homozygous GRN mutations, on the other hand, lead to complete PGRN loss and cause neuronal ceroid lipofuscinosis (NCL), a lysosomal storage disease usually seen in children. Given that the predominant clinical and pathological features of FTD and NCL are distinct, it is controversial whether the disease mechanisms associated with complete an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
159
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 165 publications
(180 citation statements)
references
References 31 publications
10
159
0
Order By: Relevance
“…In support of this idea, neurons in G rn −/− mice show pathological features similar to those seen in NCL 4447 . Similar lysosomal phenotypes have also been detected in patients with FTLD with GRN mutations 41,42 . Future studies are required to determine whether simultaneous losses of progranulin in microglia, astrocytes and neurons have synergistic effects to promote neurodegeneration (FIG.…”
Section: Future Perspectivessupporting
confidence: 71%
See 1 more Smart Citation
“…In support of this idea, neurons in G rn −/− mice show pathological features similar to those seen in NCL 4447 . Similar lysosomal phenotypes have also been detected in patients with FTLD with GRN mutations 41,42 . Future studies are required to determine whether simultaneous losses of progranulin in microglia, astrocytes and neurons have synergistic effects to promote neurodegeneration (FIG.…”
Section: Future Perspectivessupporting
confidence: 71%
“…Skin biopsy reveals lipofuscin accumulation in a vacuole-like organelle, confirming the NCL diagnosis. Interestingly, several studies show that cortical neurons and lymphoblasts from patients with FTLD with GRN mutations also contain a marked increase in lysosomal storage materials 41,42 . Together, these results further support the gene-dosage effects of progranulin deficiency in neurodegeneration.…”
Section: Progranulin Dosage and Diseasementioning
confidence: 99%
“…A recent study has also reported increased lipofuscin in heterozygous GRN mutation carriers (Ward et al, 2017). The molecular mechanisms underlying increased lipofuscin accumulation by PGRN deficiency are currently unknown.…”
Section: Discussionmentioning
confidence: 82%
“…Heterozygous GRN pathogenic variants cause about 10% of all FTD cases, while homozygous recessive pathogenic variants in GRN have been linked to recessive adult-onset NCL in two separate families [3, 6, 7, 11, 69, 79]. More recently, Ward and colleagues provided further evidence for phenotypic overlap between FTLD and NCL due to pathogenic GRN variants by identifying NCL-like biological hallmarks in haploinsufficient GRN patients [75]. Given the relationship of GRN to NCL, rare variation in other NCL genes, including CTSF, has also been suggested to contribute risk to FTD [80].…”
Section: Discussionmentioning
confidence: 99%